Rhabdomyosarcoma in the Oral Cavity of A Pediatric Patient: A Rare Case - Betül Şimşek; Esin Doğan; Didar Gürsoy Kuzuluk; Mustafa Cemaloğlu (Çocuk Dergisi)
Dear Editor, Rhabdomyosarcoma (RMS) is a rare, aggressive, and malignant neoplasm with rapid growth composed of primitive mesenchymal cells that exhibit skeletal muscle differentiation and mainly affects children and adolescents (60%) [1]. RMS is the most common soft tissue sarcoma with a rate of 50-60% in pediatric patients and ranks third among pediatric extracranial solid tumors, following Wilms tumor and neuroblastoma at a rate of 4-5% [2]. Head and neck localizations constitute 35–40% of cases, with oral lesions being extremely rare [3]. RMS has four well-defined subtypes: embryonal, alveolar, spindle cell/sclerosing, and pleomorphic. Embryonal RMS comprises 70-75% of all RMS cases [4], which are mostly sporadic. However, an increase has occurred in the number of recent studies on RMS, and the conclusions of these studies have shown that the children detected with defects in the RAS or Hedgehog pathways, as well as those with predisposing familial syndromes, carry a higher risk for developing embryonal RMS. In addition, PAX3-FOX01 and PAX7-FOXO1 fusions have been identified in alveolar RMS and been accepted as diagnostic markers by many researchers [4-7]. The literature describes the clinical signs and symptoms of oral RMS as rapidly growing swelling, facial asymmetry, paresthesia, trismus, and difficulty swallowing [1,8].